2021
DOI: 10.1186/s12933-020-01205-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of liraglutide on diastolic function parameters in patients with type 2 diabetes and coronary artery disease: a randomized crossover study

Abstract: Background Diastolic dysfunction is highly prevalent in patients with type 2 diabetes mellitus (T2DM) and is associated with overweight, glucose dysregulation and coronary artery disease (CAD). The GLP-1 receptor agonist, liraglutide, has shown to induce weight loss and improve metabolic factors, thus modulating factors associated with diastolic dysfunction. We have previously reported the effects of liraglutide on systolic function, and in this current study we explore the effects of liragluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…ree RCTs [18,20,22] presented E/e ′ at the end of the study, and the results were comparable between the liraglutide and the placebo group (I 2 � 0.0%; WMD: −0.763, 95% CI: −2.157 to 0.630, P � 0.283). Four studies [18,19,21,24] reported the outcomes of Δe ′ and ΔE/e ′ . Similarly, no statistical differences were noted between the two groups, neither Δe ′ (I 2 � 52.8%; WMD: −0.069, 95% CI: −0.481 to 0.343, P � 0.742) (Figure 4) nor ΔE/e ′ (I 2 � 53.2%; WMD: −0.683, 95% CI: −1.663 to 0.298, P � 0.172) (Figure 5).…”
Section: Left Ventricular Diastolicmentioning
confidence: 82%
See 3 more Smart Citations
“…ree RCTs [18,20,22] presented E/e ′ at the end of the study, and the results were comparable between the liraglutide and the placebo group (I 2 � 0.0%; WMD: −0.763, 95% CI: −2.157 to 0.630, P � 0.283). Four studies [18,19,21,24] reported the outcomes of Δe ′ and ΔE/e ′ . Similarly, no statistical differences were noted between the two groups, neither Δe ′ (I 2 � 52.8%; WMD: −0.069, 95% CI: −0.481 to 0.343, P � 0.742) (Figure 4) nor ΔE/e ′ (I 2 � 53.2%; WMD: −0.683, 95% CI: −1.663 to 0.298, P � 0.172) (Figure 5).…”
Section: Left Ventricular Diastolicmentioning
confidence: 82%
“…e mechanisms may involve sympathetic activity stimulation [44] and immediate effect on GLP-1 receptors in the sinoatrial node [45]. It was hypothesized that beta blocker or other heart rate-lowering drugs might blunt this potential adverse effect [18]. However, in the LIVE study, an increase in heart rate was still observed in patients treating with maximum tolerable beta-blocker dose [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, another study analysing cardiac diastolic function using echocardiography included 30 patients with type 2 diabetes in a randomized, placebo‐blinded, crossover study. The authors found no improvement in diastolic function, but did report that liraglutide reduced e' 16 …”
Section: Discussionmentioning
confidence: 93%